The comparison of Onthophagus sp. (Coleoptera: Scarabaeidae) development in forest and rubber plantation in Negeri Sembilan / Nurul Syakirah Nor Affendi, Nur Farah Atikah Anuar and Nur Hasyimah Ramli - Nor Affendi, Nurul Syakirah; Anuar, Nur Farah Atikah; Ramli, Nur Hasyimah (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Dung beetles are a valuable taxon to research disturbance due to their superiority as bioindicators of habitat quality and environmental change. They also have a significant impact on basic ecological processes such soil aeration, decomposition, nutrient recycling, secondary seed distribution, and suppression of vertebrate parasites. Although there is a growing body of knowledge regarding how species react to disturbances, studies on development seldom consider. This study aimed to determine and compare the development of Onthophagus sp. at UiTM Cawangan Negeri Sembilan forest (UiTM forest) and rubber plantation Kg. Beting, Negeri Sembilan. A total of 10 baited pitfall traps were installed systematically and left overnight for four days per sampling session, over a period of two weeks. Subsequently, the trapped samples were collected, preserved, and identified. Morphometric measurement was conducted on head width (mm) and body length (mm) and the development calculation refers to the formula: head width/ body length. The research findings indicated that O. breviconus demonstrated the greatest developmental rate range (0.0556mm) within the UiTM forest, whereas O. proletarius showcased the highest developmental rate range (0.1328mm) within the forest environment. Conversely, the O. batesi displayed the lowest rates range (0.0138mm) in UiTM forest while O. patenensis (0.0033mm) showed the lowest developmental rate range in rubber plantation. A higher development rate signifies faster growth and maturation compared to other individuals or species within the population. These findings provide valuable data for further Onthophagus sp. studies and serves as a guideline for future research and conservation efforts in Malaysia.